2008
DOI: 10.1182/blood-2007-04-081125
|View full text |Cite
|
Sign up to set email alerts
|

Gene transactivation without direct DNA binding defines a novel gain-of-function for PML-RARα

Abstract: IntroductionAcute promyelocytic leukemia (APL) is characterized by an excess of immature promyelocytes in the bone marrow that fail to differentiate toward mature granulocytes. In approximately 98% of the cases, the retinoic acid receptor-␣ (RAR␣) gene is fused to the promyelocytic leukemia (PML) gene resulting in a PML-RAR␣ fusion protein. The PML-RAR␣ chimeric protein contains most of the PML sequence and a large part of RAR␣, including its DNAand nuclear hormone-binding domains. APL blasts can be forced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…PML-RAR␣ recruitment to C/EBP␣ regulatory elements could also occur through an indirect mechanism. For instance, PML-RAR␣ has been described to interact with Sp1 55 and to repress target genes without a canonical retinoic acid response element within their promoter. 56 The C/EBP␣ proximal promoter contains 2 sites that bind to Sp1 by electrophoretic mobility shift assay (data not shown) that could enable recruitment of PML-RAR␣, and 2 potential Sp1 binding sites in the previously described methylated region upstream of the promoter.…”
Section: Org Frommentioning
confidence: 99%
“…PML-RAR␣ recruitment to C/EBP␣ regulatory elements could also occur through an indirect mechanism. For instance, PML-RAR␣ has been described to interact with Sp1 55 and to repress target genes without a canonical retinoic acid response element within their promoter. 56 The C/EBP␣ proximal promoter contains 2 sites that bind to Sp1 by electrophoretic mobility shift assay (data not shown) that could enable recruitment of PML-RAR␣, and 2 potential Sp1 binding sites in the previously described methylated region upstream of the promoter.…”
Section: Org Frommentioning
confidence: 99%
“…PML-RARA recruitment to C/EBPA regulatory elements could also occur through an indirect mechanism. Wageningen et al 19 show that PML-RARA physically interacts with Sp1 in the absence of DNA and proposed a model in which PML-RARA binds to a DNA-bound Sp1/NF-Y complex, thus modulating gene expression. The CEBPA upstream methylated region (-1423 to -1121 bp from TSS) contains two potential SP1 and USF binding sites 11 that could enable recruitment of PML-RARA.…”
Section: 18mentioning
confidence: 99%
“…Recent studies have shown that the differentiation block and the transcriptional repression induced by PML/ RARA involve not only RARA homodimerization (22), but also PML sumoylation, RXR binding, and recruitment of the polycomb complex (23)(24)(25)(26)(27). Other studies have shown that PML/ RARA may be tethered onto DNA through specific interactions with other transcription factors, identifying yet another way for the fusion to alter gene expression (28). Apart from transcriptional regulation, PML/RARA also disrupts PML nuclear bodies (29)(30)(31)(32), which regulate stem cell self-renewal (14,15,33,34), raising the tantalizing prospect that other molecular mechanisms than transcriptional repression may be implicated in APL leukemogenesis.…”
Section: Introductionmentioning
confidence: 99%